Determination of Number of Channels in Multiple Access Techniques for Wireless Communications - Venkata Raghavendra Miriampally; G. Subba Rao; V Sudheer Raja (Institute of Advanced Engineering and Science, 2015)
In wireless communications system, it is desirable to allow the subscriber to send simultaneously information to the base station while receiving information from base station. Multiple access techniques are used to allow many mobile users to share simultaneously a finite amount of radio spectrum. Frequency division multiple access (FDMA), time division multiple access(TDMA), and code division multiple access (CDMA) are the three major access techniques used to share the available bandwidth in a wireless communication system. In this paper we calculated the number of channels required for FDMA & TDMA techniques depending on various factors such as spectrum, channel band width etc.